An experimental high precision GNSS receiver for small satellites navigation - Díaz, Juan Gabriel (2017)
A new GNSS receiver intended for small satellite applications, completely designed and built in Argentina, is presented in this work. The different aspects of its architecture and design are presented, as well as the first experimental results obtained with a prototype of the GNSS receiver and a GNSS signal simulator. These tests show the excellent quality of the raw measurements produced, which are on a par with the best modern high-precision GNSS receivers and clearly indicate the high potential of the receiver for absolute and relative orbit determination.